Необходимость формирования новой политической парадигмы и перспективы региональных интеграционных проектов - Норайр Дунамалян (ՀՀ ԳԱԱ հրատ.)
Հոդվածում դիտարկվում է գլոբալ հասարակական-քաղաքական վե- րափոխման պայմաններում նոր քաղաքական հարացույցի որոնման խնդիրը, ինչպես նաև արդյունավետ անդրտարածաշրջանային ինտեգրացիոն միությունների ստեղծման հնարավորությունը համաշխարհայնացման ճգնաժամից դուրս գալու նպատակով:The article addresses the problem of finding a new political paradigm in the conditions of global socio-political transformation and the possibility of building effective transregional integrative alliances, aiming to resolve the crisis of globalization.The goal of the article is to study the underlying causes of thecurrent institutional crisis, and to attempt to find ways for solving the situation by creating a multilevel system of responding to global challenges.
Keywords: Political Science